Stable isotopes provide evidence of a trophic shift in the lesser spotted dogfish Scyliorhinus canicula from the Central Tyrrhenian Sea - REINERO, FRANCESCA ROMANA; BECERRIL-GARCÍA, EDGAR EDUARDO; ELORRIAGAVERPLANCKEN, FERNANDO R.; MELO-BARRERA, FELIPE NERI; TORALDO-SERRA, MARIA LUDOVICA; GIGLIO, GIANNI; MICARELLI, PRIMO; TRIPEPI, SANDRO; GALVÁN-MAGAÑA, FELIPE; SPERONE, EMILIO (Mediterranean Marine Science, 2023)
Stable isotopes (δ13C and δ15N) were analysed in vertebrae of Scyliorhinus canicula (n=40; 13 males, 27 females) from the central Tyrrhenian Sea to explore a potential trophic shift in relation to sex and maturity condition. Isotopic values were obtained from the centre and the periphery of the vertebra of each individual to test for the effect of maturity condition. The values of δ13C and δ15N showed significant differences between the immature and mature state of the individuals analysed (U’=1392, P<0.0001 for δ13C; U’=1385, P<0.0001 for δ15N). Differences in values of δ15N demonstrated a trophic shift during maturation progress of S. canicula. The peripheral vertebral part, corresponding to the mature state of each individual, showed higher values of δ15N (mean 5.41‰ SD±1.29‰), compared with the lower values of δ15N (mean 2.78‰ SD±1.52‰) observed in the central vertebral part related to the immature state. In contrast, the isotopic signature of δ13C was lower in the vertebral centra, and thus related to areas less enriched in C13 (mean -22.56‰ SD±1.26‰) in comparison with the vertebral periphery (mean -20.03‰ SD±1.34‰) linked to more productive environments. No significant differences in δ13C or for δ15N values were observed between sexes.